The Effectiveness of International Criminal Law in Context of Resolving Gaza-Israel Conflict - Syed Nizam Badshah Bukhari; Muaz Bukhari Syed; Sawaira Maula Dad (Dialogue Social Science Review (DSSR), 2025)
The Gaza-Israel conflict is the most enduring, and apparently intractable, in all of the modern international politics. In the face of nearly hundred years of bitter controversy both before and after the creation of Israel, many observers have come to despair that a resolution can be found. This will discuss the history of this long standing dispute and the recent events that has arose and has significantly changed the atmosphere and not only the people of Palestine but also hugely impacted the Gulf and middle eastern region. This paper will also evaluate the devastation and gruesomeness caused by Israel forces over the Gaza. Gaza also known as one of the largest open air prison in the world, where the poor residents have been kept under siege and has also denied them of their basic human rights. The wars launched over the people of Gaza not only forcefully compelled them to flee their homes and lands but also the illegal settlement left them nothing but to live in of the most densely populated place. The main aim of this paper is to evaluate the effectiveness of the international laws in this conflict. Has the international law been impactful to provide protection and basic human rights to Palestinians? Has international law ever sanctioned the Israel or held them accountable for the murders of kids, women and men and for the barbaric, inhumane satanic wars? These all factors will be discussed in this paper briefly.